Analisis Manajemen Wakaf dalam Pemberdayaan Masyarakat di Masjid Al-Munawwarah Kelurahan Penyengat Rendah Kota Jambi - Fitriyani Fitriyani; Awal Habibah (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research aims to determine waqf management in community empowerment at the Al-Munawwarah Mosque from a Sharia Financial Management perspective. This research uses a qualitative method with a descriptive analytical approach. Data was collected through interviews, observation and documentation. The research results show that waqf management at the Al-Munawwarah Mosque in the field of community empowerment has been carried out in accordance with financial management which includes collecting, developing, utilizing and reporting waqf funds. The method for collecting funds is quite good, but still needs to be improved, the use of funds is still in the refinement stage to achieve the desired goals in accordance with the objectives of the waqf. The obstacles faced are limited human resources and knowledge about effective waqf management